The delivery of nitric oxide through liposomes as next generation drug eluting stents and vascular interventions - Tan, Wei Jie (Nanyang Technological University, 2022)
The implantation of metallic stents after percutaneous coronary intervention is one form of surgical intervention to combat coronary artery disease. A major drawback is the re-narrowing or restenosis, due to the proliferation of smooth muscle cells, of the artery after a bare metal stent implantation. Stents eluting limus based drugs was then introduced to combat restenosis but resulted in new issues such as stent thrombosis. The problem lies with the non-selective nature of these drugs which inhibited the proliferation of both smooth muscle cells and endothelial cells, causing a delay in healing. This delayed healing also introduced the need for patients to undergo antiplatelet therapy which also brings forth new challenges. Hence to address the primary problem of restenosis, nitric oxide stents were explored in the past. Nitric oxide (NO) is capable of selectively inhibiting the proliferation of smooth muscle cells only, allowing for endothelial cells to proliferate and migrate. In therapy, this would promote faster and better healing for the patients. However, studies on NO releasing stents were limited and those reported had short nitric oxide release profiles. In three main studies, this thesis attempts to fabricate a nitric oxide releasing stent. To start off, three different nitric oxide donors were first examined individually. As most NO donors are water soluble, they cannot be blended with conventional polymers in organic solvents for stent spray coating. Thus, the strategy was to select one stable donor and have it encapsulated into liposomes. After which, the liposomes loaded with the donor would be coated onto the stent. Characterisation of theses donors were done via UV-VIS or with the Griess Reagent kit. It was found that endogenous s- nitrosoglutathione (GSNO) was the most stable of the three donors examined and hence was selected to be the NO donor for the stent. During the examination process, it was also found that the incorporation of NO conjugated lipids into a poly (D, L- lactide-co-glycolide) lactide:glycolide (50:50) (PLGA 50:50) blended was able to prolong the release of NO slightly. The blended film had PLGA acting as a matrix to slow down the rate of NO release via the caging mechanism. However, this fabrication was limited by significant NO loss during the drying process.